Surface-modified single wall carbon nanohorn as an effective electrocatalyst for platinum-free fuel cell cathodes - Unni, SreeKuttan M.; Ramadas, Sarath; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2015)
Platinum (Pt) and its alloys are routinely used in the cathodes of polymer electrolyte membrane fuel cells (PEMFCs) due to their high electrocatalytic activity in oxygen reduction reactions (ORRs). A variety of alternative materials have been examined as alternatives to Pt, but most of these had low activity and their performance deteriorated even further in use. In the present study an alternate electrocatalyst has been examined, obtained by a simple surface modification of single-walled carbon nanohorns by simultaneous doping with Fe and N at 900 degrees C (FeNCNH-900). This had an ORR activity superior to that of 40 wt% Pt on carbon (Pt/C). Compared to Pt/C, FeNCNH-900 gave a 30 mV improvement in onset potential and a 20 mV gain in half-wave potential in an ORR. Its high activity is the result of the simultaneous modulation achieved by the high surface area and the microporosity of carbon nanohorns, together with the establishment of the desired nitrogen-iron coordinated pyrrolic active centres. The catalyst showed excellent electrochemical stability and, most notably, its ORR activity was still increasing after 1000 cycles. Single-cell fuel cell performance using FeNCNH-900 as cathode catalyst showed a maximum power density of 35 mW cm(-2) under alkaline conditions.